(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The study is done to find out how Indian culture is portrayed through Jewelry advertisementsby selecting Kalyan Jewelers and Malabar Gold as case studies. A total of ten commercials during thetime period 2013 to 2017 have been analyzed five commercials each. Malabar Gold Diamonds is thefirst jeweler in India to focus on wedding jewelry, and at the same time, has taken steps towardspreserving and promoting the many wedding traditions across the country. Content analysis has beenused as the method of analysis on the basis of six parameters namely the advertisement appeal,communication style, cultural attributes, characters and roles represented, reflection and the theme.Keywords Indian culture, jewelers.